Effect of recombinant human bone morphogenetic protein‐2 on a novel lung cancer spine metastasis model in rodents. Issue 7 (21st January 2016) - Sonn, Kevin A.; Kannan, Abhishek S.; Bellary, Sharath S.; Yun, Chawon; Hashmi, Sohaib Z.; Nelson, John T.; Ghodasra, Jason H.; Nickoli, Michael S.; Parimi, Vamsi; Ghosh, Anjan; Shawen, Nicholas; Ashtekar, Amruta; et al.
ABSTRACT: Lung cancer is the second most prevalent cancer. Spinal metastases are found in 30–90% of patients with death attributed to cancer. Due to bony destruction caused by metastases, surgical intervention is often required to restore spinal alignment and stability. While some research suggests that BMP‐2 may possess tumorigenic effects, other studies show possible inhibition of cancer growth. Thirty‐six athymic rats underwent intraosseous injection of lung adenocarcinoma cells into the L5 vertebral body. Cells were pre‐treated with vehicle control (Group A) or rhBMP‐2 (Group B) prior to implantation. At 4 weeks post‐implantation, in vivo bioluminescent imaging (BLI) was performed to confirm presence of tumor and quantify signal. Plain radiographs and microComputed Tomography (microCT) were employed to establish and quantitate osteolysis. Histological analysis characterized pathologic changes in the vertebral body. At 4 weeks post‐implantation, BLI showed focal signal in the L5 vertebral body in 93% of Group A animals and 89% of Group B animals. Average tumor burden by BLI radiance was 7.43 × 10 3 p/s/cm 2 /sr (Group A) and 1.11 × 10 4 p/s/cm 2 /sr (Group B). Radiographs and microCT demonstrated osteolysis in 100% of animals showing focal BLI signal. MicroCT demonstrated significant bone loss in both groups compared to age‐matched controls but no difference between study groups. Histological analysis confirmed tumor invasion in the L5 vertebral body. These findings provide a reliable in vivo model to study isolated spinal metastases from lung cancer. Statement of Clinical Significance: The data support the notion that exposure to rhBMP‐2 does not promote the growth of A549 lung cancer spine lesions. © 2016 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 34:1274–1281, 2016.